Dual Effect of Structure and Hydration on Magnesium-Ion Insertion into Electrodeposited V2O5 Thin Films. Issue 11 (14th July 2020) - Henry, Hakeem K.; Johnston, Brandon; Liau, Darrin; Sahadeo, Emily; Lee, Sang Bok
Abstract : In recent years there has been some discrepancy about whether crystalline or amorphous V2 O5 is the superior cathode material for magnesium-ion batteries, with many publications suggesting that amorphous V2 O5 more readily stores magnesium ions. In this work, we report the systematic investigation of magnesium ion storage in crystalline and amorphous V2 O5 electrodeposited thin films. Our results indicate that the electrochemical performance of V2 O5 thin films is primarily impacted by the presence of adsorbed water. This study finds that the adsorbed water left over from aqueous electrodeposition is mostly responsible for the observed improved performance of amorphous V2 O5 thin films, thereby indicating that the drying conditions, rather than the crystal structure, play a direct role in enhancing the electrochemical performance. We propose an explanation for this observation in that the amorphous thin film has much larger water content, leading to increased interlayer spacing within the disordered structure and possible charge shielding for magnesium-ion storage. Ultimately, this study demonstrates the importance of considering the effect of adsorbed water, especially when comparing the electrochemical performance of amorphous and crystalline V2 O5 synthesized from wet electrodeposition techniques.